Student knowledge and pedagogical work of teachers - Arturo Comas Acuñas (Universidad del Magdalena, 2014)
it is broken down into several points collected quo beliefs that a group of students having academic class of the event, with the use of the WCC and Posac The PAP and programs. In this we include the description of the methodological design of the different stages of the investigation. The central objective of this work is to record the views of a group of students on academic class, subsequent interpretation of the results and the construction of the substantive theory.